Physiological responses to successive days of intense training in competitive swimmers - Kirwan, J. P.; Costill, D. L.; Flynn, M. G.; Mitchell, J. B; Fink, W. J.; Neufer, P. D.; Houmard, J. A (Medicine & Science in Sports & Exercise, 1988)
No improvement in either physiological tests or swimming performance was evidenced when the training distance was doubled and intensity kept constant. Implication: Once an optimal training distance (volume) is achieved, the only avenue for further improvements through physiological conditioning is through an increase in swimming intensity (quality).